Targeted suicide gene therapy for liver cancer based on ribozyme-mediated RNA replacement through post-transcriptional regulation - Seung Ryul Han; Chang Ho Lee; Ji Young Im; Ju Hyun Kim; Ji Hyun Kim; Sung Jin Kim; Young Woo Cho; Eunkyung Kim; Youngah Kim; Ji-Ho Ryu; Mi Ha Ju; Jin Sook Jeong; et al. (Elsevier, 2021)
Hepatocellular carcinoma (HCC) has high fatality rate and limited therapeutic options. Here, we propose a new anti-HCC approach with high cancer-selectivity and efficient anticancer effects, based on adenovirus-mediated Tetrahymena group I trans-splicing ribozymes specifically inducing targeted suicide gene activity through HCC-specific replacement of telomerase reverse transcriptase (TERT) RNA. To confer potent anti-HCC effects and minimize hepatotoxicity, we constructed post-transcriptionally enhanced ribozyme constructs coupled with splicing donor and acceptor site and woodchuck hepatitis virus post-transcriptional regulatory element under the control of microRNA-122a (miR-122a). Adenovirus encoding post-transcriptionally enhanced ribozyme improved trans-splicing reaction and decreased human TERT (hTERT) RNA level, efficiently and selectively retarding hTERT-positive liver cancers. Adenovirus encoding miR-122a-regulated ribozyme caused selective liver cancer cytotoxicity, the efficiency of which depended on ribozyme expression level relative to miR-122a level. Systemic administration of adenovirus encoding the post-transcriptionally enhanced and miR-regulated ribozyme caused efficient anti-cancer effects at a single dose of low titers and least hepatotoxicity in intrahepatic multifocal HCC mouse xenografts. Minimal liver toxicity, tissue distribution, and clearance pattern of the recombinant adenovirus were observed in normal animals administered either systemically or via the hepatic artery. Post-transcriptionally regulated RNA replacement strategy mediated by a cancer-specific ribozyme provides a clinically relevant, safe, and efficient strategy for HCC treatment.